Peningkatan Daya Saing UMKM Melalui Optimalisasi Penyusunan Laporan Keuangan - Wa Ode Rayyani; Muhammad Nur Abdi; Endang Winarsi; W Warda (Universitas Muhammadiyah Parepare)
This activity aims to improve the competitiveness of MSMEs by optimizing the preparation of financial statements. The background of the activity is the phenomenon of small business people, such as Micro Enterprises and Small Businesses which are generally engaged in the home industry, not yet realizing the importance of financial reports, even consider not needing financial reports because it is quite troublesome. Most transactions are recorded in memory, only a few are left in the notes that are